BETRAGTNINGER OVER KATEGORIEN INDFØDTE FOLK - Dahl, Jens (Tidsskriftet Antropologi, 1996)
Jens Dahl: Reflections on the category of Indigenous peoples The article deals with the development of the category indigenous peoples and with indigenous peoples’ position both within the thought system of the Western World and within the current work in the United Naions. It argues that the category has been created by forces in the hegemonic society, but the term has been adopted by indigenous peoples themselves, who recognize their common conditions. The term also relates to the process of decolonization and the creation of new States after the Second World War. Indigenous peoples’ demand for self determination is related to the State within which they live, and should not be understood as a violent or revolutionary demand for secession, but as a fundamental right to determine one’s own life and future.